Suture annuloplasty for surgical treatment of ischemic mitral regurgitation: long-term results - М. Л. Гордеев; А. Д. Майстренко; И. В. Сухова; Н. С. Майстренко; С. В. Исаков; А. В. Гурщенков; В. К. Гребенник (Патология кровообращения и кардиохирургия, 2015)
Oblectives. The article assesses the results of suture annuloplasty when treating ischemic mitral regurgitation (IMR). Methods. 300 patients diagnosed with ischemic heart disease after a myocardial infarction and mitral regurgitation (MR) were treated surgically between 2009 and 2013 at our center. Medical records were reviewed retrospectively to obtain clinical and echocardiographic data. Left ventricle aneurisms, II Grade mitral regurgitation and absence of structural changes in mitral valve cusps (confirmed by ECG data) were considered as criteria for selection of patients for the study. CABG and mitral suture annuloplasty were performed in all cases. The mean quantity of distal anastomoses was 3.1 0.5. Results. Hospital mortality was 11 (3.6%). All patients underwent clinical and echocardiographic follow-up at a mean period of 28.79.4 months. Overall survival was 96.26.6% at 5 years. There was a significant decrease of MR Grade before and after the operation, from 3.20.8 to 0.50.4. At 3.5 years, overall freedom from MR 3+ was 91.1 8% and freedom from MR 2+ was 75.1 8.6%. A significant decrease of mitral annulus diameter from 37.33.5 mm to 28.25.5 mm (p<0.001) was observed, without mitral stenosis though. Peak transmitral gradients were 4.83.1 mmHg before the operation and 5.52.2 mmHg after it (p>0.05). Both LV end-diastolic and end-systolic volumes indexed significantly decreased (both p=0.0001), as well as systolic pulmonary artery pressure (SPAP) (p=0.006). However, no significant increase in ejection fraction at 3.5-year follow-up (49.9 11.4% to 50.2 11.3%, p>0.05) was noted. Most patients demonstrated a reduction in NYHA class of heart failure after surgery (2.80.7 versus 0.806, p<0.001). Only 2 (3.1%) patients felt postoperative chest pain. Conclusions. Suture mitral annuloplasty is an effective technique of IMR surgical correction. It improves reverse LV remodeling. Clinically relevant mitral stenosis was not detected. It also tends to better a clinical prognosis of chronic heart failure.